Evolving multimorbidity patterns among ageing adults with cardiovascular disease continuum in Southwest China: A longitudinal cohort study - Xiaoya Qi; Ziyue Zhang; Meng Jia; Yangping Zhang; Shuang Feng; Ruixue Bai; Siyao Wang; Jinning Mao; Shu Su (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: The progression of multimorbidity in Chinese ageing adults with cardiovascular diseases remains inadequately understood. This study investigates the longitudinal evolution of cardiovascular disease continuum (CVDC)-related multimorbidity patterns in this population. Methods: The observational study analyzed medical examination reports from individuals aged 65 and older who underwent regular physical examinations during January 1, 2010 to December 31, 2022 at the Second Affiliated Hospital of Chongqing Medical University. Multimorbidity patterns of CVDC were examined. The construction of the multimorbidity network was based on Spearman correlation analyses to visualize the evolution of gender differences. Odds ratios (ORs) for developing multimorbidity in CVDC in compared to non-CVDC were calculated. Survival analysis and multivariate cox proportional hazards regression were performed to estimate the cumulative probability and identify risk factors for multimorbidity. Results: A total of 10,052 eligible individuals with 1835 (18.26 %) diagnosed with CVDC at baseline were included. The strongest positive correlation was observed between CVDC and obesity related diseases during both the initial (rmales = 0.208, rfemales = 0.244) and final (rmales = 0.312, rfemales = 0.248) examinations. Survival analysis revealed that the cumulative probability of multimorbidity of metabolic diseases in hypertension, dyslipidemia and atherosclerosis had increased over time; the corresponding adjusted HRs (95 % CIs) were 1.322 (1.219, 1.433), 1.553 (1.413, 1.706), and 1.460 (1.361, 1.567), respectively. The increasing risks of CVDC-related multimorbidity were primarily attributable to salty dietary habit (AHR = 1.336, 95 % CI: 1.239, 1.411). Conclusions: Multimorbidity patterns and disease networks associated with CVDC have become more complex over time, especially with metabolic diseases. A high-salty diet significantly increased the risk of CVDC-related multimorbidity.